Genet ic Variability and Associat ion Analysis for Grain Yield and Nutrit ional Quality in Foxtail Millet - Shingane, Smita; Gomashe, Sunil; K. N., Ganapathy; Patil, J. V. (International Journal of Bio-resource and Stress Management, 2016)
Foxtail millet is one of the climate resilient crops having great capabilities to sustain agriculture production in near future. Forty four genotypes of foxtail millet were evaluated to study the genetic variability, correlation and path coefficients. The Estimates of genotypic and phenotypic coefficients of variation were high for number of productive tillers plant-1, number of panicles plant-1, grain yield plant-1, straw yield plant-1 and iron content. All the traits except plant height had the maximum heritability. High genetic advance as per cent of mean coupled with high estimates of broad sense heritability (h2b) (>60%) indicated that, the variation observed for most of the traits were heritable and selection would be effective for improvement of these traits. Grain yield plant-1 (g) was highly significant and positively correlated with number of productive tillers plant-1, panicle length, number of panicles plant-1, 1000-grain weight, straw yield plant-1 and protein content. The selection in positive direction for these traits with grain yield plant-1 (g) can be practiced for genetic enhancement of grain yield. Path coefficient analysis revealed that 1000-grain weight had the highest positive direct effects on grain yield plant-1. The indirect effect of number of panicles, panicle length (cm), number of productive tillers and straw yield through 1000-grain weight was positive and moderate to high indicating the direct selection for 1000-grain weight in foxtail millet will lead to simultaneous indirect selection of these traits for increased grain yield plant-1.